Breaking up the global value chain : opportunities and consequences - Pedersen, Torben, active 2017; Devinney, Timothy M. 1956-; Camuffo, Arnaldo, active 2017 (Advances in international management ;, 2017)
With intensified global competition, institutional changes and reduced communication costs the propensity of firms to reconfigure their global value chain and separate their activities across national boundaries has increased markedly. It enables firms to combine the benefits arising from specialization and increased flexibility with location advantages. Consequently, large parts of manufacturing and other more standardized activities have been offshored to emerging countries. However, recent developments are challenging this traditional separation between advanced and emerging economies as host of knowledge- and production-intensive activities, respectively. Recent research has emphasized the role of intra-organizational relationships and links among the different parts of the value chain. Innovative and productive activities are affected by strong interdependencies and complementarities, and for some companies the co-location of R&D and manufacturing is critical for development and innovation. This volume will interest scholars in International Business, Economic Geography, Operations and Supply Chain Management, International Economics, and Political Science.